Genetics, biochemistry and structure of the archaeal virus STIV. (20th January 2009) - Fulton, Jennifer; Bothner, Brian; Lawrence, Martin; Johnson, John E.; Douglas, Trevor; Young, Mark
Abstract : STIV ( Sulfolobus turreted icosahedral virus) has been the subject of detailed structural, genetic, transcriptomic, proteomic and biochemical studies. STIV arguably has been investigated in more detail than any other archaeal virus. As a result, we know more about STIV than other viruses infecting members of the Archaea domain. Like most viruses isolated from crenarchaeal hosts, STIV has little in common with viruses that infect eukaryotic and bacterial hosts and should be considered the founding member of a new virus family. However, despite this lack of obvious homology with other viruses, STIV has components of gene content, replication strategy and particle structure reminiscent of viruses of the Eukarya and Bacteria domains, suggesting an evolutionary relationship between viruses from all domains of life. The present mini-review describes the current knowledge of this virus and insights it has given us into viral and cellular evolution, as well as newly developed tools for the further study of STIV–host interactions.